2016
DOI: 10.11157/anzswj-vol28iss1id114
|View full text |Cite
|
Sign up to set email alerts
|

Consent, coercion and autonomy: Underage sex work in Aotearoa New Zealand

Abstract: INTRODUCTION:Adolescents' involvement in sex work in New Zealand has been associated with a range of adverse effects on physical, psychological, and social well-being, and is framed by domestic legislation and international obligations. AIM:The study aimed to ascertain the nature of adolescents' experiences of sex work, and how their current and past environments impacted on their understanding of their involvement in sex work. METHODS:Semi-structured interviews were used with a sample of eight adolescents age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…That report found that there was no substantial difference in the violence or sexual abuse suffered by sex workers in the country and 35% of sex workers stated that they had been coerced into prostitution. On the issue of trafficking, several scholars have strongly denied and contested claims that there has been no trafficking in New Zealand since the passage of the PRA, see, e.g., [19,20]. These scholars point to two key elements to counter claims that sex trafficking has decreased in or disappeared from New Zealand.…”
Section: Criminalization and Decriminalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…That report found that there was no substantial difference in the violence or sexual abuse suffered by sex workers in the country and 35% of sex workers stated that they had been coerced into prostitution. On the issue of trafficking, several scholars have strongly denied and contested claims that there has been no trafficking in New Zealand since the passage of the PRA, see, e.g., [19,20]. These scholars point to two key elements to counter claims that sex trafficking has decreased in or disappeared from New Zealand.…”
Section: Criminalization and Decriminalizationmentioning
confidence: 99%
“…There is no official screening process for the identification of victims and, therefore, no possibility of such victims securing access to needed medical, psychological, social, or legal resources. Some of these scholars even argue that the continued discourse about the lack of trafficking in New Zealand means that any disclosures by trafficking victims are likely to be misinterpreted and ignored [19].…”
Section: Criminalization and Decriminalizationmentioning
confidence: 99%
“…It has been argued that unsolicited dick pics are a form of online sexual harassment, yet the normalisation of men's sexual intrusions may mean they are not always framed as such (Hayes & Dragiewicz, 2018;Salter, 2016;Thorburn, 2018). Although several participants described persistent requests for nudes and unsolicited sexual images as unwanted and annoying, they did not often speak about these interactions in a way that made strong links to sexual harassment and gendered abuse.…”
Section: The Pressure To Send Nudesmentioning
confidence: 99%
“…The precursors to this marginality (such as histories of abuse or abandonment) create immense vulnerability, which is identified and capitalized on by traffickers who can entice victims with promises of basic essentials and emotional security (Dorais & Corriveau, 2009; Hanna, 2002; Parker & Skrmetti, 2013; Reid, 2016). However, it is unknown to what extent this is the case in Aotearoa New Zealand, although research into underage sex work suggests that histories of abuse and family marginality are instrumental in shaping adolescent girls’ entry into self-facilitated sex work (Thorburn, 2016).…”
Section: Domestic Sex Trafficking Contextsmentioning
confidence: 99%